2003
DOI: 10.1383/medc.31.3.112.28495
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Tuberculosis

Abstract: Tuberculosis (TB) can involve any part of the gastrointestinal tract from mouth to anus, the peritoneum and the pancreatobiliary system. It can have a varied presentation, frequently mimicking other common and rare diseases 1. The clinician must look for tuberculosis, and confirm or exclude this treatable malady in any patient who presents with gastrointestinal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 23 publications
2
32
1
2
Order By: Relevance
“…Contrary to the earlier reports, the developing countries are showing a fearful increase in the incidence of abdominal tuberculosis, as reported in recent studies [20][21][22]. The increase in the prevalence of abdominal tuberculosis in the developing countries is attributed to a rising incidence of HIV-positive population linking it to immunosuppression [12,19].The age incidence of our study population coincides with other similar reports [20]. The male dominance is very clear in our studies as reported by other similar studies [18].…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Contrary to the earlier reports, the developing countries are showing a fearful increase in the incidence of abdominal tuberculosis, as reported in recent studies [20][21][22]. The increase in the prevalence of abdominal tuberculosis in the developing countries is attributed to a rising incidence of HIV-positive population linking it to immunosuppression [12,19].The age incidence of our study population coincides with other similar reports [20]. The male dominance is very clear in our studies as reported by other similar studies [18].…”
Section: Discussioncontrasting
confidence: 93%
“…The unusual presentation and confusion in diagnosis usually lead to unnecessary and avoidable laparotomies, which is most of the time performed as a last resort to reach to a conclusive diagnosis. Contrary to the earlier reports, the developing countries are showing a fearful increase in the incidence of abdominal tuberculosis, as reported in recent studies [20][21][22]. The increase in the prevalence of abdominal tuberculosis in the developing countries is attributed to a rising incidence of HIV-positive population linking it to immunosuppression [12,19].The age incidence of our study population coincides with other similar reports [20].…”
Section: Discussionsupporting
confidence: 60%
“…In areas of high‐TB prevalence, empiric treatment for TB with careful clinical review is often resorted to when diagnostic uncertainty exists 53 . This approach is problematic as it may delay treatment for CD or make it difficult to confirm or refute a diagnosis of ITB at a later stage.…”
Section: The Clinical Differences Between Crohn’s Disease and Intestimentioning
confidence: 99%
“…In developed nations, TB is a disease of immigrants, the indigent or institutionalized or occurs in the immunosuppressed. In areas of high‐TB prevalence, the disease is of the young or middle‐aged with no distinguishing demographics 51, 53 . Intuitively the duration of symptoms would seem a distinguishing feature, but both diseases have an insidious onset which may go undiagnosed for many years 55 .…”
Section: The Clinical Differences Between Crohn’s Disease and Intestimentioning
confidence: 99%
See 1 more Smart Citation